Dynamics of stimulated luminescence in natural quartz: Thermoluminescence and phototransferred thermoluminescence - Folley, Damilola Esther (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2020)
Natural quartz has remained an important mineral that is of topical interest in luminescence and dosimetry-related research. We investigate the dynamics of stimulated luminescence on this material through thermoluminescence (TL) and phototransferred thermoluminescence (PTTL). Measurements were made on unannealed natural quartz as well as quartz annealed at 800 and 1000ÌŠC. The samples were annealed for 10 minutes and for 1 hour. The material, in its un- and annealed state has its main peak between 68 and 72ÌŠC when measured at 1Cs Ìƒ1 after a dose of 50 Gy. A study of dosimetric features and kinetic analysis was carried out on two prominent peaks, peak I and III for all the samples. The peaks show a sublinear dose response for irradiation doses between 10 and 300 Gy. Kinetic analysis shows that peak I is a first-order peak and peak III a general-order peak. Interestingly, we observe for peak I for the sample annealed at 800ÌŠC for 1 hour an inverse thermal quenching behaviour. We demonstrate that a peak affected with an inverse thermal quenching-like behaviour can still show effect of thermal quenching when the dose the sample is irradiated to is significantly reduced. We ascribe the apparent dependence of thermal quenching on dose to competition between radiative and non-radiative transitions at the recombination centre. Peaks I, II, and III for all the samples were reproduced under phototransfer when the peaks, initially removed by preheating to a certain temperature are exposed to 470 and 525 nm light. The infuence of duration of illumination on the PTTL intensity of these peaks corresponding to various preheating temperatures is modelled using coupled first-order dfferential equations. The model is based on systems of acceptors and donors whose number and role depends on preheating temperature
Keywords: Thermoluminescence; Quartz